Capping non-economic awards in medical malpractice trials : California jury verdicts under MICRA - Pace, Nicholas M. (Nicholas Michael), 1955-; Golinelli, Daniela; Zakaras, Laura; Rand eBooks (Santa Monica, CA : RAND, 2004)
Concerns over the price and availability of medical malpractice insurance have sparked a vigorous national debate over proposed federal legislation calling for limits on trial awards and attorneys' fees in medical malpractice cases. A model for such limits is the Medical Injury Compensation Reform Act (MICRA), a law enacted in California in 1975 in the hope of controlling soaring medical malpractice insurance premiums and ensuring the continuing availability of malpractice insurance coverage. MICRA caps awards for non-economic losses, such as pain or suffering, at $250,000 and limits plaintiffs' attorney fees. The authors studied the effects of MICRA on plaintiffs' awards and on defendants' liabilities and in doing so addressed a number of questions: How have MICRA's caps on non-economic damages affected the final judgments in California jury trials? What types of cases and claims are most likely to have an award cap imposed following trial? What have been the effects of MICRA on plaintiffs' attorney fees and net recoveries? If the MICRA cap had been adjusted for inflation, what would have been the effect on plaintiffs' final awards?
"RAND Institute for Civil Justice."
Includes bibliographical references (p. 79-83).
Also available on the internet via WWW in PDF format.
Keywords: Compensation (Law) -- California; Insurance, Physicians' liability -- California; Medical personnel -- Malpractice -- California; Electronic books